Radiation induced segregation near dislocations and symmetric tilt grain boundaries in Fe-Cr alloys: A phase-field study. (15th February 2022) - Moladje, G.F. Bouobda; Thuinet, L.; Becquart, C.S.; Legris, A.
Abstract: A phase-field model dedicated to dislocation climb under irradiation has been coupled to point defects and chemical species transport equations. It allows to predict radiation induced segregation in Fe-Cr alloys around dislocations in the isolated or stacking configuration like in symmetric tilt grain boundaries. This work is challenging for several reasons: (i) radiation induced segregation in Fe-Cr is difficult to simulate since Cr depletion or enrichment can occur, depending on the Cr nominal composition and temperature, (ii) dislocations are biased sinks due to their elastic fields which can not be ignored in this case and (iii) other surrounding microstructural defects can interact with dislocations and impact point defect and solute transport. To overcome (iii), a mean-field approach is adopted, in which the influence of the surrounding sinks is taken into account through the introduction of an overall and uniform sink strength in the point defect diffusion equations. Despite the numerous parameters of the model, unknown experimental information and approximations made to make the simulations tractable, the numerical results are in good agreement with the experimental ones. Moreover, the model allows to identify the main physical parameters to correctly quantify radiation induced segregation in the case of dislocations. Among them, the point defect relaxation volumes are of first importance in comparison with the solute relaxation volume or the nature of the slip system.